Obtención de biodiesel a partir de la grasa de pollo - Del Castillo Mori, Hernando (2024)
The general objective of the work was to obtain biodiesel from chicken fat, with specific objectives: Evaluate the preliminary treatment process of impurities in chicken fat, evaluate the transesterification process by applying catalysts, and determine the physical and chemical characteristics of the biodiesel obtained. It has a quantitative approach, technological application, according to the thesis students' intervention it is pre experimental. The study population is the supply centers that sell chicken to the public, the sampling is probabilistic, the sample size was 3000 g of chicken fat, the processing of the raw material (chicken fat) was carried out in laboratory, using the transesterification process; More relevant results were obtained than the Methanol/Oil molar ratio, (6/1), it had a higher yield that was greater than 80%, so it is recommended that this alternative to obtain biodiesel should be taken into consideration, taking into account Keep in mind that the raw material is disposed of in municipal dumps, so the product obtained (biodiesel) must be evaluated, which has 12% oxygen in its chemical composition, which is why it is added to a petroleum derivative. (diesel-2), which when reacted in internal or external combustion engines, reduces the emission of carbon dioxide, which is a greenhouse gas.